Transcription Factor SlAREB1 Is Involved in the Antioxidant Regulation under Saline-Alkaline Stress in Tomato - Zijian Xu; Fan Wang; Yongbo Ma; Haoran Dang; Xiaohui Hu (MDPI AG, 2022)
Basic leucine zipper (bZIP) transcription factors of the ABA-responsive element binding factor/ABA-responsive element binding proteins (ABF/AREB) subfamily have been implicated in abscisic acid (ABA) and abiotic stress responses in plants. However, the specific function of ABF/AREB transcription factors under saline-alkaline stress is unclear. Here, we identified four ABF/AREB transcription factors in tomato and found that SlAREB1 strongly responded to both ABA and saline-alkaline stress. To further explore the function of SlAREB1 under saline-alkaline stress, SlAREB1-overexpressing lines were constructed. Compared with wild-type plants, SlAREB1-overexpressing transgenic tomato plants showed reduced malondialdehyde content, increased the relative water content, and alleviated the degradation of chlorophyll under saline-alkaline stress. Importantly, SlAREB1 directly physically interacted with SlMn-SOD, which improved the activity of antioxidant enzymes and increased the scavenging of excess reactive oxygen species. Overall, the overexpression of SlAREB1 increased the antioxidant capacity of the transgenic tomato under saline-alkaline stress.